Cross-protection induced by highly conserved human B, CD4+, and CD8+ T-cell epitopes-based vaccine against severe infection, disease, and death caused by multiple SARS-CoV-2 variants of concern - Prakash, Swayam; Dhanushkodi, Nisha R.; Zayou, Latifa; Ibraim, Izabela Coimbra; Quadiri, Afshana; Coulon, Pierre Gregoire; Tifrea, Delia F.; Suzer, Berfin; Shaik, Amin Mohammed; Chilukuri, Amruth; Edwards, Robert A.; Singer, Mahmoud; et al. (Frontiers in Immunology, 2024)
Background: The Coronavirus disease 2019 (COVID-19) pandemic has created one of the largest global health crises in almost a century. Although the current rate of SARS-CoV-2 infections has decreased significantly; the long-term outlook of COVID-19 remains a serious cause of morbidity and mortality worldwide; with the mortality rate still substantially surpassing even that recorded for influenza viruses. The continued emergence of SARS-CoV-2 variants of concern (VOCs), including multiple heavily mutated Omicron sub-variants, have prolonged the COVID-19 pandemic and underscores the urgent need for a next-generation vaccine that will protect from multiple SARS-CoV-2 VOCs. Methods: We designed a multi-epitope-based Coronavirus vaccine that incorporated B, CD4+, and CD8+ T cell epitopes conserved among all known SARS-CoV-2 VOCs and selectively recognized by CD8+ and CD4+ T-cells from asymptomatic COVID-19 patients irrespective of VOC infection. The safety, immunogenicity, and cross-protective immunity of this pan-variant SARS-CoV-2 vaccine were studied against six VOCs using an innovative triple transgenic h-ACE-2-HLA-A2/DR mouse model. Results: The pan-variant SARS-CoV-2 vaccine: (i) is safe; (ii) induces high frequencies of lung-resident functional CD8+ and CD4+ TEM and TRM cells; and (iii) provides robust protection against morbidity, virus replication. COVID-19-related lung pathology and death caused by six SARS-CoV-2 VOCs: Alpha (B.1.1.7), Beta (B.1.351), Gamma or P1 (B.1.1.28.1), Delta (lineage B.1.617.2) and Omicron (B.1.1.529). Conclusions: A multi-epitope pan-variant SARS-CoV-2 vaccine bearing conserved human B and T cell epitopes from structural and non-structural SARS-CoV-2 antigens induced cross-protective immunity that facilitated virus clearance, and reduced morbidity, COVID-19-related lung pathology and death caused by multiple SARS-CoV-2 VOCs.